2015
DOI: 10.5114/aoms.2015.56358
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and management of male lower urinary tract symptoms: treatment patterns and guidelines in a correlation study among Polish urology consultants

Abstract: IntroductionIn March 2013, the European Association of Urology (EAU) released a new edition of the guidelines on management of male lower urinary tract symptoms (LUTS), including benign prostatic obstruction. The objective of this study was to evaluate how well the EAU guidelines have been implemented in day-to-day practice by Polish urologists.Material and methodsA structured questionnaire, which explored how urologists diagnose and manage male lower urinary tract symptoms, was emailed to all certified, activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 12 publications
2
3
0
Order By: Relevance
“…Our real-life data concerning current pharmacotherapy for benign prostate enlargement (BPE) shows that ARAs monotherapy remains as the most frequent therapeutic option utilized in more than one-third of patients. It is in line with the survey performed among Polish urologists, showing that ARAs in monotherapy was the first line option for patients with and even without BPE [13]. When comparing the prescribed medication for non-neurogenic LUTS with the data coming from PolSenior study [15], performed in years 2007 -2012, one may see that the prescription of ARAs in monotherapy has declined from 64.7 to 25.6%, during last years, possibly as a consequence of later guidelines from 2010.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our real-life data concerning current pharmacotherapy for benign prostate enlargement (BPE) shows that ARAs monotherapy remains as the most frequent therapeutic option utilized in more than one-third of patients. It is in line with the survey performed among Polish urologists, showing that ARAs in monotherapy was the first line option for patients with and even without BPE [13]. When comparing the prescribed medication for non-neurogenic LUTS with the data coming from PolSenior study [15], performed in years 2007 -2012, one may see that the prescription of ARAs in monotherapy has declined from 64.7 to 25.6%, during last years, possibly as a consequence of later guidelines from 2010.…”
Section: Discussionsupporting
confidence: 88%
“…In parallel, during this period of time there was an increase in the utilisation of ARA+5αRI combined therapy from 21.9% to 30.9% and most spectacularly the use of MRAs (in the combined therapy) from 1.7 to 23.6%. The increase in the utilization of MRAs, revealed by our observation, is in line with the treatment option accepted by 83.7% of Polish urologists concerning MRAs use for the management of storage LUTS [13]. While the most recently introduced drug -mirabegron is currently rarely used (1.4% of overall study population and 2.4% of those with storage symptoms), probably due to the lack of reimbursement from Polish National Health Fund.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Data regarding guideline adherence are important because they provide comparative benchmarks and identify potential areas of intervention [2]. In concordance with "treat-to-target" principles [3], evidence-based European League Against Rheumatism (EULAR) guidelines for rheumatoid arthritis (RA) advocate early and individualized treatment [4].…”
Section: Introductionmentioning
confidence: 99%
“…Early studies have indicated that approximately half of patients receive the recommended care in chronic conditions, and this remains true when considering screening, diagnosis, treatment and follow-up [ 1 ]. Data regarding guideline adherence are important because they provide comparative benchmarks and identify potential areas of intervention [ 2 ]. In concordance with “treat-to-target” principles [ 3 ], evidence-based European League Against Rheumatism (EULAR) guidelines for rheumatoid arthritis (RA) advocate early and individualized treatment [ 4 ].…”
Section: Introductionmentioning
confidence: 99%